2022
DOI: 10.3390/ijerph19063303
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Perceived Household Financial Decline Due to COVID-19 and Smartphone Dependency among Korean Adolescents

Abstract: This cross-sectional study identified the association between COVID-19-related perceived household financial decline and smartphone dependency among adolescents in South Korea. Data from the 2020 Youth Risk Behavior Survey of Korea was used and 54,809 middle and high school students were included. COVID-19-related perceived household financial decline was categorized as no financial decline, mild, moderate, and severe. Smartphone dependency was calculated by 10 questions and was largely categorized as yes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Currently, several studies have identified factors causing mobile phone addiction during the COVID-19 pandemic. For example, household financial decline due to COVID-19, peer phubbing, interpersonal alienation, loneliness, escape motivation, perceived stress, and social cynicism have been reported to be significant positive predictors of mobile phone addiction [23][24][25][26][27][28]. Kayis et al [10] conducted a questionnaire survey among 773 adults and determined that the fear of COVID-19 had a significant positive predictive effect on mobile phone addiction.…”
Section: Covid-19 Victimization Experience and Mobile Addictionmentioning
confidence: 99%
“…Currently, several studies have identified factors causing mobile phone addiction during the COVID-19 pandemic. For example, household financial decline due to COVID-19, peer phubbing, interpersonal alienation, loneliness, escape motivation, perceived stress, and social cynicism have been reported to be significant positive predictors of mobile phone addiction [23][24][25][26][27][28]. Kayis et al [10] conducted a questionnaire survey among 773 adults and determined that the fear of COVID-19 had a significant positive predictive effect on mobile phone addiction.…”
Section: Covid-19 Victimization Experience and Mobile Addictionmentioning
confidence: 99%
“…The following items were used: “Do you think the household financial status of your families has become more difficult than before due to COVID-19?” Response options are on a 4-point Likert scale: strongly no, no, yes, and strongly yes. We have operationalized these response options into “no decline,” “mild decline,” “moderate decline,” and “severe decline,” aligned with the previous study ( Jung et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies reported an increased prevalence of obesity and overweight among adolescents during the pandemic [ 5 ], as well as an increased prevalence of anxiety when families experienced economic difficulties due to COVID-19 [ 6 ]. Smartphone usage and alcohol consumption among adolescents increased during the pandemic, particularly in families experiencing economic difficulties [ 7 , 8 ]. These findings suggest that COVID-19 significantly affected the daily lives of Korean adolescents and that the alterations in household economic status because of COVID-19 influenced their lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%